Evaluasi Metode Perbaikan Tanah Lunak dengan Preloading Kombinasi PVD-PHD pada Proyek Pembangunan Jalan Tol Semarang-Demak Paket II - Irvita Asri Aini; Eggy Ihza Maulana; Hinawan Teguh Santoso (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
Soil condition in the construction of the Semarang-Demak II Toll Road Project on the northern coast of Java Island is dominated by soft soil. Soft soil has the potential to cause problems such as relatively low permeability, poor bearing capacity, and large long-term settlements that will cause damage to the construction above it in the future. Therefore, it is necessary to improve the soft soil capacity, one of which is the Preloading and PVD-PHD combination method. This study aims to evaluate the value of settlement and consolidation time of embankment on soft soil between design and construction. The research method is carried out by field investigation/survey methods to obtain data on the settlement magnitude and consolidation time of embankment, and find possible causes of differences. The study found that there were differences in the value of the settlement and the consolidation time between the design and actual conditions in the field. The final settlement when the degree of consolidation reached 90% was observed to be almost the same between the design and actual condition, where the difference was 0.0063 meters or 2.81%. However, a significant difference was found between the time of consolidation for design and construction, which was 28 days (14.70%) faster than the estimation time. Factors that influence the difference in consolidation time, include: the volume weight of the preloading embankment in the field is 1.65 kN/m3 (9.70%) higher than the plan, the embankment elevation in the field is 0.237 meters (3.36%) higher than the design, and the use of drainage well to dissipate water trapped in the “trap-zone” in the middle of the embankment.